Dramatic reduction of clindamycin serum concentration in staphylococcal osteoarticular infection patients treated with the oral clindamycin-rifampicin combination. Issue 2 (August 2015) - Bernard, Aurélie; Kermarrec, Gwénolé; Parize, Perrine; Caruba, Thibaut; Bouvet, Anaïs; Mainardi, Jean-Luc; Sabatier, Brigitte; Nich, Christophe
Summary Objectives Pharmacokinetics of clindamycin in combination with rifampicin or levofloxacin were prospectively evaluated for the oral treatment of severe staphylococcal osteo articular infections. Methods Thirty-four patients (25 males, 9 females), with a mean age of 52.4 ± 17 years (range, 24–81 years), were randomly assigned either to the clindamycin-rifampicin or to the clindamycin-levofloxacin arm (control), following surgical debridement and intravenous adapted treatment. Trough and peak serum concentrations of clindamycin were measured at day-1 (D1), D15 and D30 of oral treatment. Cure was evaluated at a minimum of one year after the initiation of treatment. Results The oral treatment was interrupted in 4 cases because of adverse events. Mean trough and peak serum concentrations of clindamycin in the clindamycin-rifampicin arm were lower than in the clindamycin-levofloxacin arm during the time of oral antibiotic regimen (0.79 ± 0.3 μg/ml vs 4.7 ± 1.2 μg/ml, p < 0.001, and 3.48 ± 1.1 μg/ml vs 10.2 ± 1.8 μg/ml, p < 0.001, respectively). A consistent decrease in clindamycin serum concentration was observed at each time-point of follow-up. At a mean of 23 ± 7.8 months (range, 12–47 months), 24 patients were available for clinical evaluation. No difference could be detected in the cure rates between the groups. Conclusions Our results indicate a significant influence of rifampicin on clindamycin pharmacokinetics using the oral route. Clindamycin serum concentrations (trough and peak) were systematically below the recommended therapeutic ranges when associated with rifampicin, as opposed to the control. Considering the potential risk of selection of mutant resistant to clindamycin, we do not recommend the clindamycin-rifampicin combination in the oral treatment of severe staphylococcal osteoarticular infection, unless clindamycin serum concentration is thoroughly controlled. The study has been registered on the clinicaltrials.gov website under the number NCT 01500837.